Pendekatan Kualitatif dan Kuantitatif : Suatu Telaah - Arditya Prayogi; Irfandi; M. Arif Kurniawan (Complex : Jurnal Multidisiplin Ilmu Nasional, 2024)
Based on the underlying approach, in general, two types of research can be distinguished, namely research with a qualitative approach and research with a quantitative approach. The two approaches have different assumptions, goals, characteristics and procedures. The aim of this article is to understand conceptually the various fundamental characteristics of each approach. The method used in writing this article is literature study by collecting library sources and reconstructing them. The result is that the qualitative approach makes all aspects of human life the object of study. For this reason, the qualitative approach has become very synonymous with the field of human sciences. Meanwhile, the quantitative approach describes natural (and also social) phenomena using numbers, which requires measuring the level of certain characteristics of an observed phenomenon. The different paradigms of quantitative and qualitative approaches cause the research processes and results of the two approaches to be different.